2020
DOI: 10.3390/su12051855
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Ambient Fine Particulate Matter on Consumer Expenditures

Abstract: Airborne particulate matter suspended from industrial facilities, power plants, and automobiles is detrimental to health. Growing concerns about the increasing level of airborne particulate matter have led many industrialized nations to advocate for the transformation of the energy market and investment in sustainable energy products. At the other end, consumers have made individual adjustments and attempted to reduce the exposure to the particulate matter. In this paper, we focus on the effect of ambient air … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…The feature importance analysis revealed a striking shift in the importance of PM 10 as a predictor of quarterly sales before and during the COVID-19 pandemic. Pre-pandemic, PM 10 ranked as the 10th most important feature, highlighting its importance to sales forecasting [46]. This suggested that, in the absence of external shocks, environmental factors like air quality played a noteworthy role in shaping sales predictions [47].…”
Section: Discussionmentioning
confidence: 99%
“…The feature importance analysis revealed a striking shift in the importance of PM 10 as a predictor of quarterly sales before and during the COVID-19 pandemic. Pre-pandemic, PM 10 ranked as the 10th most important feature, highlighting its importance to sales forecasting [46]. This suggested that, in the absence of external shocks, environmental factors like air quality played a noteworthy role in shaping sales predictions [47].…”
Section: Discussionmentioning
confidence: 99%